Rehabilitation of nazism as a crime in the Criminal Code of the Russian Federation (Ius Novum, 2023)
The paper discusses with the crime of rehabilitation of Nazism contained in the 1996 Criminal Code of the Russian Federation. It presents the rationale for its introduction into the legislation, the scope of the legal regulation, and its evaluation in terms of its content and edition. For the purpose of the publication, research questions were posed, the answers to which demonstrated the political and populist nature of the regulation and its imprecise casuistic approach, which brings few benefits to Russia’s criminal policy.
Keywords: Nazism; rehabilitation of Nazism; criminal code of the Russian Federation